Pengaruh Penggunaan Filler dalam Pengeringan terhadap Perubahan Komponen Nutrisi dalam Penyimpanan Hasil Olahan Limbah Organik Dapur dan Restoran Hotel - Bambang Sulistiyanto; Sri Sumarsih; C Imam Sutrisno; Nurwantoro Nurwantoro; Istiyan PM; Anum D (Caraka Tani: Journal of Sustainable Agriculture, 2005)
Research of effect filler addition in drying to nutrient component exchange in storage of processed organic wastes of kitchen and restaurant hotel’s was done at the laboratory of feed Technology, Departemen of Animal Nutrition and Feeding, Faculty of Animal Science UNDIP, Semarang. The research was aimed to study effect of filler addition in drying process of organic wastes of kitchen and restaurant hotel’s so the qualityy of product observed from proximate component and total fungi exchange during storage. Experiment was conducted by factorial completely randomized design (CRD-factorial) 3x2x3. Organic wastes of hotels class 1,2 and 3 dried by adding filler 0 and 15% and were stored for 0, 4 and 8 weeks. Component proximate i.e.: crude protein (CP), crude fat (CF), crude fiber (CF), Ash and Nitrogen Free extract (NFE) and total fungi are parameter observed. Data were statistically analyzed by Steel and Torrie (1981).The result showed that interaction effects of rice brand addition and time of storing are significant to EE, CF and NFE (P<0.05), but the effect to CP and Ash are not significant (P>0.05). interaction between hotel class, filler and storing significantly affected total fungi in the processed product (P<0.05).